Argument and Performance: Alcibiades’ Behavior in the Symposium and Plato’s Analysis in the Laws - Erler, Michael (Peitho. Examina Antiqua, 2017)
Argument and literary form, and how they both relate to each other, are crucial aspects of any interpretation of the Platonic dialogues. Plato the author and Plato the philosopher always work hand in hand in that Plato the author tries to serve Plato the philosopher. It is, therefore, an appropriate principle for approaching the study of Plato’s philosophy to take into account the literary aspects of the dialogues and to ask how Plato’s literary art of writing could possibly support his philosophical message and, for instance, to consider what this relation means in the context of the debate about developementalism versus unitarianism in Plato’s philosophy. In the present paper , I argue that the performance of the characters plays an important role in this context. I discuss various passages in the Laws which analyse the weakness of the will and I compare what Plato says there with the performance of Alcibiades in the Symposium. I conclude that the passages in the Laws can be read as a kind of commentary on Alcibiades’ behavior and I consider what this relation means in the context of the debate about developementalism versus unitarianism in Plato’s philosophy.